A cultura da renda de bilro na Prainha/Aquiraz-CE: o processo educativo na produção do artesanato - Cavalcante, Natalia Mikaely da Silva (2024)
The general objective of this work is to analyze the dimensions of the educational process in the production of bobbin lace crafts, as an object of transformation of the scenario of exploitation and devaluation of craft work for women who produce bobbin lace, in a way delimited to reality. of the lacemakers of Prainha de Aquiraz-Ce. And as specific objectives: Identify how the teaching of the practice of bobbin lace and the process of apprehending it are established; investigate working conditions and how lacemakers have capitalized on income production amidst a scenario of exploitation and devaluation of these artisans' workforce, present in the marketing of their products. To examine, therefore, how this educational process in the transfer of knowledge, of artisanal work, has transformed the local reality of artisans. The method that underpins this study is historical-dialectical materialism and the methodological path takes on a qualitative nature, materialized through bibliographical and field research, which used participant observation, semi-structured interviews and the field diary instrument as techniques. The work is structured in three parts: The first part we begin with the survey of the central problem of our research regarding the educational process in the artisanal work of bobbin lace, as a basis; then we aim for a discussion anchored in Marxian-Lukacsian ontology, returning to the writings that deal with the ontological relationship between the founding category of social being (work) initially placed by Marx in the work of Capital and by Lukács (1979) as the category of departure for the investigation of subsequent social phenomena and the complexes founded by him suitable for the analysis of language and education. It is from these basic authors and their interpreters that we guide the research. The second part fulfills an introductory role of general presentation of the research; addressing the discussion about craftsmanship and the historicity of bobbin lace, as well as its development as a craft in the Northeast and, more precisely, in Ceará, to emphasize the territory under analysis which is Aquiraz-Ce, with an emphasis on the relationship between with the female workforce. To cover the historical aspects of the craft, we are based on studies by Luiza Ramos and Arthur Ramos (1948), Armelle Enders (2012), and Valdenice Carneiro Girão (2013). To reflect on female work and the job market, we used the analyzes of Lina Bo Bardi (1994); Eunice Ribeiro Durham (1983); Paulo Freire (1999); Helena Hirata (2016), Eric J. Hobsbawm (1984) and Maria Lúcia Martinelli (2001). Among other sources consulted. The third part presents empirical data. Thus, with the aim of learning about the daily life of the bobbin lace trade, we enter into the discussion about the educational process mediated by sociability and non- formal education, carried out in line with the transfer of knowledge, where we end by giving visibility to the reality of lacemakers in the little beach of Aquiraz-Ce and his craft.